Translation of cytochrome f is autoregulated through the 5′ untranslated region of petA mRNA in Chlamydomonas chloroplasts - Choquet, Y. (The National Academy of Sciences, 1998)
A process that we refer to as control by epistasy of synthesis (CES process) occurs during chloroplast protein biogenesis in Chlamydomonas reinhardtii: the synthesis of some chloroplast-encoded subunits, the CES subunits, is strongly attenuated when some other subunits from the same complex, the dominant subunits, are missing. Herein we investigate the molecular basis of the CES process for the biogenesis of the cytochrome b(6)f complex and show that negative autoregulation of cytochrome f translation occurs in the absence of other complex subunits. This autoregulation is mediated by an interaction, either direct or indirect, between the 5′ untranslated region of petA mRNA, which encodes cytochrome f, and the C-terminal domain of the unassembled protein. This model for the regulation of cytochrome f translation explains both the decreased rate of cytochrome f synthesis in vivo in the absence of its assembly partners and its increase in synthesis when significant accumulation of the C-terminal domain of the protein is prevented. When expressed from a chimeric mRNA containing the atpA 5′ untranslated region, cytochrome f no longer showed an assembly-dependent regulation of translation. Conversely, the level of antibiotic resistance conferred by a chimeric petA-aadA-rbcL gene was shown to depend on the state of assembly of cytochrome b(6)f complexes and on the accumulation of the C-terminal domain of cytochrome f. We discuss the possible ubiquity of the CES process in organellar protein biogenesis.